FINANCIAL EDUCATION ON THE BENEFITS AND RISKS OF USING FINTECH FOR GENERATION Z AT INSTIKI - I Dewa Ayu Agung Tantri Pramawati; Kompiang Martina Dinata Putri; I Putu Arya Mulyawan (Sean Institute, 2023)
This research was conducted to provide literacy education to Generation Z, namely students about the benefits and risks, as well as how to be wise in using financial technology or FinTech. This literacy education is a very important enrichment for students amid the rapid innovations that occur in the trend of digital financial transactions and have not been widely elaborated in the campus curriculum. Studying this phenomenon, students must be introduced more closely to the benefits and risks of using financial technology or Fintech through the learning video